Desain Didaktis Berbasis GeoGebra pada Materi Bangun Ruang Sederhana - Yanti, Indres Novri; Risnawati; Hamdani, M. Fikri (Journal of Practice Learning and Educational Development, 2026)
This study aims to develop a GeoGebra-based didactic design for simple spatial figures to overcome learning obstacles experienced by elementary school students. The method used is Didactical Design Research (DDR), which consists of three main stages: analysis of the didactic situation before learning, metapedagogical observation, and retrospective analysis of the suitability of the design with the learning process that occurs. Data were obtained through diagnostic tests of learning obstacles, observations, and interviews with teachers and fifth-grade students at SDN 007 Bonai Darussalam. The results showed that students experienced epistemological obstacles in understanding spatial figure networks, identifying spatial figure elements, and distinguishing the properties of blocks and cubes. Traditional learning that only uses static images makes it difficult for students to visualize three-dimensional shapes as a whole. The initial didactic design was then revised by integrating concrete, semi-concrete, and digital activities using GeoGebra. The implementation of the revised didactic design showed an increase in students' understanding in connecting 2D and 3D representations, recognizing spatial elements, and understanding the concept of similarity through interactive visual exploration. Overall, the GeoGebra-based didactic design proved effective as a learning innovation that strengthened students' understanding of geometry and improved the quality of the teaching and learning process.